Effect of taurine supplementation on preventing ventilator-associated pneumonia in pediatrics under mechanical ventilation, a randomized controlled double-blind clinical trial - Shirzad-Yazdi, Nasrin; Shorafa, Eslam; Abootalebi, Seyedeh Narjes; Heidari, Reza; Hojabri, Katayoon; Doostfatemeh, Marziyeh; Masjedi, Fatemeh; Vazin, Afsaneh; Shafiekhani, Mojtaba (Frontiers in Pediatrics, 2025)
IntroductionOne of the most prevalent healthcare-associated infections in the pediatric intensive care unit is ventilator-associated pneumonia (VAP). VAP not only results in prolonged hospital and intensive care unit (ICU) stays but also imposes higher costs on patients and the healthcare system. Therefore, it is essential to implement preventive measures. The lung-protective properties of taurine are recognized, and this research focuses on assessing the impact of taurine supplementation in preventing VAP.MethodThis double-blind, randomized clinical trial was conducted at Namazi Hospital's PICUs. The study included pediatrics on mechanical ventilation for over 48 h. Patients were randomly divided into two groups: the taurine and placebo groups. Alongside the standard care, participants from both groups were administered taurine or placebo capsules (30 mg/kg. day) in divided doses from the day of PICU admission through PICU discharge. The incidence of VAP through clinical and laboratory evidence was considered the primary outcome.ResultsSeventy-seven patients were included in the study, with 38 in the taurine group and 39 in the placebo group. VAP incidence was 7.9% in the taurine group and 64.1% in the placebo group. Taurine significantly reduced the duration of mechanical ventilation, ICU and hospital stay, and inotrope duration. The occurrence of septic shock was lower in the taurine group at 5.3%. Stepwise logistic regression showed that placebo receipt was the only risk factor for VAP, with placebo recipients being 20.8 times more likely to develop VAP. (P < 0.0001, OR 20.8, 95% CI 6.11–97.93) Taurine treatment also significantly reduced inflammatory markers such as CRP, pro-calcitonin, and interleukin-6 compared to placebo.ConclusionOur results showed that taurine supplementation can reduce the incidence of VAP and the duration of mechanical ventilation, ICU, and hospital stay in critically ill pediatric patients. Registration number of the clinical trialThis study received approval from the Iranian registry clinical trial, registered on 29 June 2023 (IRCT20120731010453N4, http://www.irct.ir/).